ENVIRONMENTAL HYGIENE AND MICROBIOLOGICAL ASSESSMENT OF FOOD SERVICE ESTABLISHMENTS IN SELECTED BOARDING HIGH SCHOOLS IN IBADAN, NIGERIA (2023)
Schools’ Food Service Establishments (FSEs) have been incriminated in numerous foodborne diseases outbreaks globally and have been linked to the environment and food handling procedures in the establishments. Despite this, FSEs in Nigerian boarding schools have been poorly investigated. In order to provide baseline data for infection control, this study was designed to assess environmental hygiene and food handlers’ Knowledge, Attitude and Practices (KAP) and investigate food-related microbial contamination from selected boarding schools’ FSEs in Ibadan, Nigeria.Observational checklist and interviewer-administered questionnaire were used to evaluate environmental hygiene parameters, food handlers’ KAP in four schools’ FSEs out of forty-three schools by inclusion criteria and balloting. Swabs from Food Contact Surfaces (FCS): utensils and surfaces; 20 food handlers’ hands and samples of Ready to-Eat (RTE) foods were examined for Aerobic Plate Count (APC), Total Coliform (TC), Faecal Coliform (FC) and selected important foodborne pathogens counts using standard methods. Isolated bacteria were characterised phenotypically and subjected to 16S rRNA sequencing. Antibiotic susceptibility testing was determined using disc diffusion and E-strip techniques based on CLSI and EUCAST standards, respectively. Data were analysed using descriptive statistics and ANOVA at α0.05. Schools FSEs’ compliance mean scores for environmental hygiene parameters were 82.2, 56.8, 52.7 and 65.6% for toilets, dining areas, kitchens and observed food handlers at work, respectively. The food handlers had good knowledge (61.9%), positive attitude (81.4%) to ensure food safety, but poor hygiene practices (52.6%) which differed significantly among schools (p=0.012, χ2=10.15). Major unsanitary practices observed were: use of basins and buckets for dish washing, uncovered solid waste receptacles, non-availability of sanitising agents and inadequate handwashing. Mean logCFU/cm2 of APC for counter tops, chopping boards, grinders, trays and knives were 5.59±1.56, 4.38±2.62, 4.01±0.77, 2.47±2.23 and 2.38±1.75, respectively. Food handlers’ hands’ mean logCFU/cm2 of APC, TC, FC, Staphylococcus and Bacillus species were 3.10±1.78, 2.62±1.23, 2.80±1.74, 1.94±1.04 and 1.97±1.39, respectively. Seventy-eight percent of RTE foods conformed to acceptable limit of < 4logCFU/g for APC. The distribution of bacteria from schools FSEs were 62.0% (FCS), 19.0% (food handlers’ hands) and 19.0% (RTE foods). The identified food-related bacteria were Alcaligenes faecalis, Achromobacter xylosoxidans, Bacillus cereus, Ochrobactrum anthropi,viiiProteus mirabilis, Serratia marcescens, Staphylococcus saprophyticus and Bordetella species. Alcaligenes faecalis resistance (%) to cefixime, cefuroxime, ceftazidime, gentamicin, augmentin, nitrofurantoin, ofloxacin and ciprofloxacin were 76.2, 71.4, 66.7, 61.9, 57.1, 42.9, 4.8 and 4.8, while for Bacillus cereus, they were 85.7,100.0, 57.1, 85.7, 28.6, 57.1, 0.0 and 0.0, respectively. The minimum inhibitory concentration of colistin for Alcaligenes faecalis ranged from 1.5 µg/mL to >256 µg/mL which was highly significant (F=9.194, p<0.05) compared to other antibiotics. Two Bacillus cereuswere resistant to imipenem, 81.0% were multi-antibiotic resistant, while none of the identified bacteria showed resistance to piperacillin/tazobactam.Food contact surfaces and food handlers’ hands were grossly contaminated. The presence of colistin-resistant Alcaligenes faecalis and resistance of Bacillus cereus to imipenem in boarding schools’ food service establishments is a serious public health concern. These findings will be useful in policy formulation and the development of food safety guidelines in boarding schools.